Teaching Catholic Social Thought Online in the Philippines: From a Challenge to an Opportunity - Teofilo Giovan S. Pugeda III (Journal of Moral Theology, 2022)
In this article, I build the case that students learn Catholic social thought (CST) best by experiencing it pedagogically. To do so, I share the following: Ateneo de Manila University’s experience in transitioning to online teaching in response to a global pandemic; my experience in designing a CST course that considers the limitations of online teaching, makes use of its strengths, and inspires greater awareness of local issues; and my experience in teaching the course. With these three sections, five suggestions for CST pedagogy are proffered for consideration by other CST teachers. As such, this essay may serve as another reference for those interested in the pedagogical changes brought about by a global pandemic as well as a meaningful contribution from the Philippines to the development of a CST pedagogy.